Distortion in Fingerprints: A Statistical Investigation using Shape Measurement Tools1. Issue 4 (20th May 2014) - Sheets, H. David; Torres, Anne; Langenburg, Glenn; Bush, Peter J.; Bush, Mary A.
Abstract Friction ridge impression appearance can be affected due to the type of surface touched and pressure exerted during deposition. Understanding the magnitude of alterations, regions affected, and systematic/detectable changes occurring would provide useful information. Geometric morphometric techniques were used to statistically characterize these changes. One hundred and fourteen prints were obtained from a single volunteer and impressed with heavy, normal, and light pressure on computer paper, soft gloss paper, 10‐print card stock, and retabs. Six hundred prints from 10 volunteers were rolled with heavy, normal, and light pressure on soft gloss paper and 10‐print card stock. Results indicate that while different substrates/pressure levels produced small systematic changes in fingerprints, the changes were small in magnitude: roughly the width of one ridge. There were no detectable changes in the degree of random variability of prints associated with either pressure or substrate. In conclusion, the prints transferred reliably regardless of pressure or substrate